Literasi Digital Dan Lingkungan Kerja Terhadap Kinerja Pegawai Dengan Perilaku Kerja Inovatif Sebagai Variabel Intervening - Metris, Diksi; Priambodo, Aji (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2023)
The aim of this research is to analyze the influence of digital literacy and work environment on the performance of employees with innovative work behavior as an intervening variable in Puskemas Kutasari District, Purbalingga, Central Java. To achieve this goal, primary data was used using the Likert scale 5-point survey method to gather data from respondents using the SmartPLS application. The study used quantitative analysis and structural equation modeling (SEM) to test seven hypotheses related to the relationship between digital literacy, work environment, innovative work behavior, and employee performance. The results showed that digital literature directly influences innovative employee behavior, digital literation influences employee achievement, the work environment does not influence employee performances, the working environment influences innovative work behaviors, and the employee’s performance through innovative work conduct.